The Role of Students in Improving the Quality of Education and Community Religion - Sri Ramayanti; Melina Hasanahti; Annisa Rahmi Rambe (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The religious quality of a person cannot be judged by the quantity of worship he performs in the mosque or prayer room. The religious quality of a person can be judged from how sincere he is in socializing with society and nature. This paper attempts to describe the role of real working group students (KKN) at UIN North Sumatra Medan in improving the religious quality of the community during the month of Ramadan in Hessa Perlompongan Village. The method used in this paper is a qualitative descriptive study method. Data collection is based on reports that researchers collect in KKN activities in Hessa Perlompongan Village, through interviews, observations, and documentation. The results of this study indicate that UIN North Sumatra Medan students who carry out KKN in Hessa Perlompongan Village are happily welcomed by the community during the month of Ramadan. This is due to the role of students in inviting the community to prosper the mosque, making positive activities for children, and filling Ramadan activities with worship rituals and lectures "spiritual showers".